PENGARUH TOTAL ASSET TURN OVER (TATO) DAN EARNING PER SHARE (EPS) TERHADAP RETURN SAHAM PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BEI PERIODE 2012-2016 - Maiyaliza, Maiyaliza (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2017)
This research aims to determine the effect of each a Total Asset Turn Over (TATO) and Earning Per Share (EPS) of the Stock Return on Food and Beverage companies registered in the Indonesian Stock Exchange (BEI) in the period 2012-2016. This research was conducted using secondary data. Sample selection technique used is purposive sampling technique, from 14 companies only taken eight companies that match the criteria used. The analytical method used is simple linear regression analysis and multiple linear regression analysis. The results of this study have fulfilled classical assumption test. This research also used hypothesis test the are partial test and simultaneous test. Data were analyzed using SPSS 23:00 for windows. From the regression results indicate that the Total Asset Turn Over (TATO) and Earning Per Share (EPS) respectively no significant effect on Stock Return and jointly Total Asset Turn Over ( TATO ) and Earning Per Share ( EPS ) respectively no significant effect on Stock Return . Keywords : Total Asset Turn Over, earning Per Share, Stock Return